2017
DOI: 10.1590/s1984-29612016088
|View full text |Cite
|
Sign up to set email alerts
|

Trombiculiasis in domestic goats and humans in the state of Maranhão, Brazil

Abstract: Trombiculiasis is an infestation caused by larval mites (chiggers) of the family Trombiculidae. Here, we provide the first report on parasitism by the chigger species Eutrombicula alfreddugesi (Oudemans) and Eutrombicula batatas (Linnaeus) in goats and humans on farms in the state of Maranhão, northeastern Brazil. Severe itching and dermatitis caused by the chiggers' bites were seen. From a total of 779 examined goats, 214 of them showed clinical signs of infestation, as well as family members of three farms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Confalonieri and De Carvalho (1973) found E. batatas parasitizing G. domesticus in Mangaratiba (Rio de Janeiro). This species was also found parasitizing equines in Cáceres (Mato Grosso) (Confalonieri and Benez 1976) and on goats in Maranhão state (Faccini et al 2017). …”
Section: Checklist Of Larvae Chigger Species (In Alphabetical Order) mentioning
confidence: 91%
See 1 more Smart Citation
“…Confalonieri and De Carvalho (1973) found E. batatas parasitizing G. domesticus in Mangaratiba (Rio de Janeiro). This species was also found parasitizing equines in Cáceres (Mato Grosso) (Confalonieri and Benez 1976) and on goats in Maranhão state (Faccini et al 2017). …”
Section: Checklist Of Larvae Chigger Species (In Alphabetical Order) mentioning
confidence: 91%
“…There are additional records from Chapada do Araripe (Ceará) on Tropidurus hispidus (Squamata) (Delfino et al 2011) and from Morro do Chapéu (Bahia), on Tropidurus hispidus , Tropidurus cocorobensis , Tropidurus semitaeniatus and Tropidurus erythrocephalus (Menezes et al 2011). Recently this species was found parasitizing goats in Maranhão state (Faccini et al 2017). …”
Section: Checklist Of Larvae Chigger Species (In Alphabetical Order) mentioning
confidence: 99%
“…Although the propensity of chiggers to cause pruritic dermatitis is well recognised in humans and other animals [35-38], the identity of the allergens involved has not been established [110]. The L. deliense and D. tinctorium genomes were predicted to encode 37 and 33 groups of protein allergens, respectively; substantially more than other sequenced mites in the Acariformes with the exception of the dust mites, D. farinae [77] and E. maynei [111].…”
Section: Analysesmentioning
confidence: 99%
“…[34]. Furthermore, chiggers have direct impacts worldwide by causing trombiculiasis, which is a highly pruritic dermatitis that can afflict humans, companion animals and domestic ruminants, potentially leading to severe hypersensitivity [35-38].…”
Section: Introductionmentioning
confidence: 99%
“…They had contact with parrots and capybaras (Hydrochoerus hydrochaeris). Faccini et al (2017) reported cases of trombiculiasis in goats and humans in the state of Maranhão.…”
Section: Discussionmentioning
confidence: 99%